Bilateral Vestibulopathy Aggravates Balance and Gait Disturbances in Sensory Ataxic Neuropathy, Dysarthria, and Ophthalmoparesis: A Case Report. Issue 1 (September 2016) - van Leeuwen, Roeland B.; Smits, Bart W.; Rodenburg, Richard J.; van Engelen, Baziel G.
Abstract : Abstract: In patients with a triad of sensory ataxic neuropathy, dysarthria, and ophthalmoparesis (SANDO), the presenting features are mainly ataxia or ptosis. SANDO patients often have impaired balance and gait, which is not surprising considering the combination of sensory ataxic neuropathy, and additional symptoms like cerebellar ataxia and limb girdle weakness. We describe a SANDO patient who noticed an increasingly impaired balance and gait, without any dizziness. Neurological investigation revealed an external ophthalmeplegia and a cerebellar ataxia; the head impulse test was not reliable because of eye movement disorders. The caloric reflex tests showed lack of responses on both sides, compatible with severe bilateral vestibulopathy. Making the diagnosis of bilateral vestibulopathy in SANDO patients may have implications for the management of the patient, because specific vestibular rehabilitation can improve gaze and postural stability.